The importance of Information and Communication Technologies (ICT) to promote Information, self-care and empowerment among patients with chronic illnesses - Sá, C.; Oliveira, A.; Nabais, A. (10th International Conference on Education and New Learning Technologies, EDULEARN18, 2018)
In the last decades, there has been some technical-scientific advances in the healthcare domain, enabling us to live longer. This reality is particularly important for people suffering from chronic diseases, because they have to find adequate ways to manage their limitations and healthcare condition. Therefore, self-care promotion is one of the biggest challenges of healthcare, particularly for nurses. At the same time, technologies are increasingly used methods by patients to search for information and knowledge about their diseases. With this paper, we intend to verify in what extent does Information and Communication Technologies (ICT) may help patients with chronic diseases to promote their self-care and to manage their health condition. In this sense, we conducted a systematic literature review, focused in following databases: Medeline, Cinahl, PubMed e SciencHub. The main key-words that were used in this research were: chronic disease, self-care, self-management and information systems. We found results from previous works evidencing that patients with chronic diseases resort online information sources (considered reliable), to acquire information that help their self-efficacy and self-management of health condition. The communication or collaborative tools used are primarily the email, discussion forums, blogs and social media. Online programs of self-management of chronic illness also contribute to a faster communication stream between patients and health professionals, in order to allow feedback and social support, having a positive impact in patients’ behaviors, in terms of their adherence and therapeutic management, and also improving health care demand. Thus, we acknowledge that the use of ICT, using various types of media (smartphone, tablet, notebook, ...), not only promotes health education, self-care and empowerment, but also facilitates the communication between patients and health professionals. So, ICT is a relevant contribution to chronic diseases’ patients, facilitating their lives at different levels, and in particular, providing adequate tools to deal with their situation.